Comparison of the different operation room environmental exposures on tear film function before and after operation - Yufei Dang; Ming Zhang; Yanqiang Wei; Na Duan; Linjuan Zhang; Rujia Liu; Zhen Zhang; Yue Zhang; Li Li (Heliyon, 2024)
1.2 Previous studies have confirmed that air and light pollution can cause damage to a number of systems throughout the body, including the ocular surface and retina. However, the exact effect of air pollution and light pollution on tear film function is not clear. This study explored the different operation room environmental exposures on tear film function before and after operation. Sixty medical staff in the operating room were selected and divided into 4 groups according to different surgical methods to evaluate the tear film function before and after operation: Da Vinci surgery group (DVSS), Laparoscopic surgery group (LS), Traditional surgery group (TS), and Ophthalmic microsurgery group (OM). The results showed that the levels of light and air pollution were elevated in operating rooms during the operation and the changes of tear film function in the other three groups were statistically significant except for DVSS group. In TS group, particulate matter (pm) 1 (R = 0.61, p < 0.01), pm2.5 (R = 0.63, p < 0.01), and pm10 (R = 0.67, p < 0.01) were positively correlated with eye redness index, and first and average noninvasive tear film break-up times were positively correlated with illuminance (R = 0.54, p < 0.05; R = 0.97, p < 0.01). In OM group, there was a positive correlation between the operation time and the first (R = 0.69, p < 0.01) and average (R = 0.89, p < 0.01) noninvasive tear film break-up times. Our research found that exposure to different operating room environment will lead to damage of tear film function, but also provide a theoretical basis for the improvement of surgical environment.